Multimedia Web Development As Video Viewing Media With Php In Local Network - Tiara Putra (Jurnal Mandiri IT, 2020)
Exploring content collections is one of the things that internet cafe users do that is highly expected by managers. Activities carried out to select collections that are interesting and entertaining or even needed by users. This research was conducted with the aim of developing a web-based software to help explore the available film collections, (2) ensuring the quality of the software developed in accordance with the ISO 25010 standard on aspects of functional suitability, usability, and reliability. The research methodology used is Research and Development (R&D) with a waterfall development model. This development model has stages starting from analysis, design, implementation and research testing. The results of this study are: (1) an information system to assist the browsing of film collections for internet café users. (2) the system has met the software quality standard according to the ISO 25010 standard in the functional suitability aspect of 100% (very good), usability aspect of 75.97% (good), and 100% reliability aspect.